Immersive Technologies in Deaf and Hard of Hearing (DHH) Mathematics Education: Narratives from Augmented Reality to the Metaverse - Chong, Ai Peng; Wong, Kung-Teck; Kong, Vestly Liang Soon (Journal of Research, Innovation, and Strategies for Education (RISE), 2025)
This narrative review critically examines the role of immersive technologies, including augmented reality (AR), virtual reality (VR), mixed reality (MR), and the metaverse, in enhancing mathematics learning for Deaf and Hard-of-Hearing (DHH) students. These learners often encounter challenges such as limited communication access, restricted academic sign language vocabulary, and difficulties in understanding abstract concepts, which contribute to persistent achievement gaps and mathematics anxiety. Immersive technologies provide new opportunities through three-dimensional visualization, manipulation of virtual objects, and avatar-based interactivity that can enrich comprehension and engagement. This review adopts a narrative approach to synthesize evidence from multiple disciplines, including education, psychology, information technology, and computer science. The focus is on studies retrieved from major databases such as Scopus, Web of Science, IEEE Xplore, Semantic Scholar, and Google Scholar, along with other sources related to mathematics and DHH learners. The findings indicate that AR, VR, and MR are effective in visualizing mathematical concepts and strengthening spatial reasoning, while the metaverse extends these affordances by enabling collaborative learning, social presence, and accessibility features such as captions and sign-language avatars. Nevertheless, challenges remain, including the high cost of devices, uneven infrastructure, limited teacher readiness, and inconsistent accessibility design. This review emphasizes the need for large-scale longitudinal studies, the development of Universal Design for Learning (UDL)-based frameworks, and cost-effectiveness evaluations to ensure that the integration of immersive technologies is inclusive, sustainable, and effective in mathematics education for DHH learners.
Keywords: immersive technology; augmented reality; metaverse; mathematics; deaf and hard of hearing (DHH)